Analysis of the Quality of Gerobak Cinta Services in Handling Stunting Rates in Larantuka District, East Flores Regency - Adolfina Gerans , Magdalena; Mustofa, Amirul; Sarwani (Publikauma : Jurnal Administrasi Publik Universitas Medan Area, 2023)
This research aims to analyze the service quality of Gerobak Cinta and its impact on stunting rates in Larantuka District, East Flores Regency. The method used in this research is qualitative. Research data was obtained through observations of the running of the Gerobak Cinta program, interviews with related integrated service post cadres, and submission of documents at the health center and the East Flores District Health Service. The research results show that the Gerobak Cinta supplementary food program implemented in East Flores Regency is considered high quality. The quality of service in this program results in better fulfillment of community nutrition from the supplemental food program. Ultimately, this program reduced the stunting rate significantly based on the previous year's stunting data. This research implies that the Gerobak Cinta supplementary food program needs to be increased evenly in all sub-districts in East Flores Regency. Stunting will be as low as possible if this program can be expanded and its quality improved.